IBM PowerHA SystemMirror V7.2.3 for IBM AIX and V7.2.2 for Linux - Quintero, Dino (IBM Redbooks, 2019)
This IBM® Redbooks® publication helps strengthen the position of the IBM PowerHA® SystemMirror® for Linux solution with well-defined and documented deployment models within an IBM Power Systems"!environment, which provides customers a planned foundation for business resilience and disaster recovery (DR) for their IBM Power Systems infrastructure solutions. This book addresses topics to help answer customers' complex high availability (HA) and DR requirements for IBM AIX® and Linux on IBM Power Systems servers to help maximize system availability and resources and provide technical documentation to transfer the how-to-skills to users and support teams. This publication is targeted at technical professionals (consultants, technical support staff, IT architects, and IT specialists) who are responsible for providing HA and DR solutions and support for IBM PowerHA SystemMirror for AIX and Linux Standard and Enterprise Editions on IBM Power Systems servers